Implant Survival and Clinical Outcomes of Total Hip Arthroplasty in Adolescent and Young Adult Patients - Zeitlinger, Lauren; Gemayel, Anthony; Whitlock, Patrick; Sorger, Joel (The Journal of Hip Surgery, 2021)
Total hip arthroplasty (THA) in pediatric patients is controversial with concern for high failure rates, and lack of promising outcomes as compared with the adult population. Increased survivorship of implants invites the potential for improved function and quality of life in young adults. Although THA is now an option for end-stage symptomatic hip disease in young patients, outcomes with contemporary techniques and implants have yet to be reported.Following the institutional review board approval, a retrospective chart review of 25 patients (29 hips) with end-stage hip disease at a single institution from 2010 to 2017 was performed. All patients underwent THA with noncemented, contemporary THA with highly cross-linked polyethene liners. Clinical, radiographic, and patient-reported outcomes were obtained including any postoperative complications, revisions, evidence of loosening or wear, and lastly, Western Ontario & McMaster Universities Osteoarthritis Index, Harris Hip Scores, Non-Arthritic Hip scores, and International Hip Outcome Tool. With a minimum follow-up duration of 2 years, there were no revisions or evidence of loosening or wear on follow-up radiographs. All patients underwent noncemented THA with metal or ceramic on highly cross-linked polyethylene liners. Six patients accounting for seven THAs completed patient-reported outcomes: two reporting excellent outcomes, four good outcomes, and one failed outcome. With advancing techniques and strategies, treatment options for hip pathology in the pediatric population are growing. We present favorable outcomes 2 years post-procedure, suggesting THA as a potential option for end-stage hip disease in pediatric and young adult patients.
Keywords: total hip arthroplasty; end-stage hip disease; hip preservation; survivorship